Enhancing secondary school students' achievement in chemistry using explicit embedded and activity-based reflective strategies (2023)
This paper determined the effects of explicit embedded and activity-based reflective strategies on secondary school students' achievement in chemistry in Akinyele Local Government, Oyo State. The study comprised of Senior Secondary School II (SS2) chemistry students selected from six randomly selected secondary schools. Intact of SS2 chemistry classes were used in the study. The instruments used to collect data were Students' Organic Chemistry Achievement Test (r=0.80) and instructional guides. Data collected were subjected to the Analysis of covariance at 0.05 level of significance. The results revealed that there was significant main effect of treatment on students’ achievement in Chemistry (F(2,103>-225.97; p<0.05, partial η2=0.81). The participants in Activity- based Reflective Strategy (x= 16.86) performed better than their counterparts in Explicit Embedded Reflective Strategy (ẋ =15.33), and Conventional Strategy (ẋ =5.73). It was therefore recommended that explicit-embedded and activity-based reflective learning strategies should be adopted by the teachers in order to enhance their achievement in chemistry.